Synthesis and In Vitro Testing of Mg-6Zn-xHAp Biocomposites from Beef Bone as Biodegradable Bone Implant Material - Manalu, Jojor Lamsihar; Tjhay, Francisca; Kristoforus, Theodora; Aritonang, Sovian (Universitas Negeri Malang, 2024)
This study aimed to develop biodegradable Mg-6Zn hydroxyapatite (Mg-6Zn HAp) biocomposites for potential use in bone replacement applications. The hydroxyapatite (HAp) powders, sourced from cow bone, were synthesized through an eco-friendly and cost-effective process, leveraging bioresources for material sustainability. The Mg-6Zn and HAp powders were mechanically mixed through ball milling for six hours to ensure homogeneity. The resultant powder mixture was then subjected to isostatic pressing at a high pressure of 570 MPa, forming a dense coin-shaped composite with a 1.5 cm diameter. This coin was consolidated in a capsule furnace at elevated temperatures for one hour to enhance material integrity. The Mg-6Zn HAp alloy was thoroughly characterized using X-ray diffraction (XRD) to assess phase formation and crystallographic structure, and Scanning Electron Microscopy coupled with Energy Dispersive X-ray Spectroscopy (SEM-EDX) to examine microstructural features and elemental composition. For composite preparation, varying amounts of HAp (5%, 8%, and 12%) were incorporated into the Mg-6Zn matrix. SEM analyses revealed a uniform distribution of HAp particles along the boundaries of matrix particles, enhancing composite structure and stability. Results demonstrated that with an increase in HAp content, there was a corresponding improvement in the relative density and hardness of the composites. The corrosion rate decreased with higher HAp content, indicating improved biocompatibility and stability in physiological environments. This suggests that the Mg-6Zn HAp biocomposites, with their tailored microstructure and enhanced mechanical properties, hold promise for use in biodegradable bone replacement applications.